The Effectiveness of Google Sites in Differentiated Instruction to Increase Students’ Learning Motivation and Reading Comprehension on English Narrative Texts - Najemi, Silvia; Ardiasih, Lidwina Sri; Sundari, Hanna (Universitas Lancang Kuning, 2024)
This research explores the impact of using Google Sites for Differentiated Instruction on the learning motivation and reading comprehension of Grade XI students at SMK Negeri 4 Banjarmasin. The study aims to enhance literacy by integrating digital media into English narrative text instruction. A quasi-experimental design was employed, with an experimental group using Google Sites and a control group using conventional methods. Data were collected through pre-tests and post-tests measuring reading comprehension and questionnaire to describe learning motivation. The Independent Sample T-Test, Mann Whitney Test and N-Gain, and Multivariate Analysis of Variance (MANOVA) were used for statistical analysis. The results indicated that the experimental group showed significant improvements in both learning motivation and reading comprehension compared to the control group. The use of Google Sites provided a personalized and engaging learning experience, contributing to these positive outcomes. In conclusion, integrating Google Sites into Differentiated Instruction effectively enhances students' motivation and reading comprehension. This approach addresses individual learning needs and leverages technology to create a more interactive educational environment. The study suggests broader implementation of digital tools in education to improve literacy skills and student engagement.